Dynamic analysis of the input-controlled buck converter fed by a photovoltaic array - Villalva,Marcelo Gradella (2008)
The control of the input voltage of DC-DC converters is frequently required in photovoltaic applications. In this special situation, unlike conventional converters, the output voltage is constant and the input voltage is controlled. This paper deals with the analysis and the control of the buck converter with constant output voltage and variable input.